DEVELOPMENT OF AN ORGANIC WASTE MANAGEMENT MODEL IN BAN BOK COMMUNITY, NONG KHAI NOK SUBDISTRICT, MUEANG SAM SIP DISTRICT, UBON RATCHATHANI PROVINCE - Sukhonthachit, Penmat; Chada, Wilawun; Duangsri, Jaruporn; Thanee, Kidsada (Life Sciences and Environment Journal, 2025)
This study aimed to develop a participatory model for organic waste management in Ban Bok, Nong Khai Nok Subdistrict, Mueang Sam Sip District, Ubon Ratchathani Province, Thailand. The research adopted a Participatory Action Research (PAR) approach utilizing the PAOR process—Planning, Action, Observation, and Reflection—divided into two phases: (1) assessing the current problems and management practices of organic waste in the community, and (2) collaboratively developing and implementing a context-appropriate model. A total of 113 household members participated through purposive sampling. Data collection included both quantitative and qualitative methods. Quantitative data were collected via pre- and post-intervention surveys to assess participants' knowledge, attitudes, and behaviors regarding organic waste management. Qualitative data were gathered through focus group discussions, observation, and field notes. Results indicated significant improvements across all dimensions after a 3-month intervention. High knowledge levels increased from 0.9% to 16.8%, positive attitudes from 7.1% to 30.1%, and proper behaviors from 3.5% to 11.5%. Mean scores for knowledge rose from 11.54 to 13.44, attitude from 3.11 to 3.47, and behavior from 2.77 to 3.20 (p-value < 0.001). The community effectively adopted the systematic separation of organic waste and utilized it through composting, bio-fermentation, and animal feed. The model proved to be effective, practical, and adaptable to similar rural communities, promoting sustainable waste management aligned with local lifestyles